2020
DOI: 10.1021/acs.inorgchem.9b03433
|View full text |Cite
|
Sign up to set email alerts
|

Activating Water and Hydrogen by Ligand-Modified Uranium and Neptunium Complexes: A Density Functional Theory Study

Abstract: Organometallic uranium complexes that can activate small molecules are wellknown. In contrast, there are no known organometallic trans-uranium species capable of smallmolecule transformations. Using density functional theory, we previously showed that changing actinide-ligand bonds from U−O groups to Np−N− (amide/imido) bonds makes redox smallmolecule activation more energetically favorable for Np species. Here, we determine how general this ligand-modulation strategy is for affecting small-molecule activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Very recently, Odoh and co-workers have embarked on a theoretical study, where the variation from uranium–oxygen bonds to neptunium–amide/imido ones was centered on. They found that the water reduction reaction was energetically possible (Chart d) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Odoh and co-workers have embarked on a theoretical study, where the variation from uranium–oxygen bonds to neptunium–amide/imido ones was centered on. They found that the water reduction reaction was energetically possible (Chart d) …”
Section: Introductionmentioning
confidence: 99%
“…They found that the water reduction reaction was energetically possible (Chart 1d). 38 In the work, the dihydrogen production catalyzed by ( Me,Me ArO) 3 ArAn (An = Ac−Pu) has been comprehensively investigated using relativistic DFT calculations. The various intermediates along the catalytic pathway have been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, understanding the neptunium-based compounds has great significance in the safe handling and separations of highly radioactive nuclear waste. 2 In the past few decades, neptunium-based compounds have been intensively investigated and discussed through experiments [4][5][6] and computations 7,8 as the long-lived Np can prolong the long-term radiotoxicity of the waste, among which neptunium hydrides are extremely reactive and decompose above 573 K in vacuum, yielding finely divided pyrophoric elemental neptunium. Some research suggests that neptunium hydrides have generally been used to prepare other neptunium-based compounds, such as NpN x , 9 NpC x , 10 NpS x , 11 NpAs x , 12 and NpSe x .…”
Section: Introductionmentioning
confidence: 99%